Green reverse logistics technology impact on agricultural entrepreneurial marketing firms’ operational efficiency and sustainable competitive advantage. - Ernest Mugoni; Brighton Nyagadza; Precious Kuziva Hove (Sustainable Technology and Entrepreneurship, 2023)
The purpose of the study is to analyse how green reverse logistics technology impacts agricultural entrepreneurial marketing firms’ operational efficiency and sustainable competitive advantage. Systematic literature review and meta-analytical methodology was adopted to execute the current study. Reverse Logistics Model has been used for the current study as the theoretical model grounding the study as it enables a quick reaction and finding resolution for the customer return whilst regaining the highest value that is possible on each returned item. Results indicate that green reverse logistics technology has a strong influence on agricultural entrepreneurial marketing firms’ operational efficiency and sustainable competitive advantage. The study further shows existing research gaps that can be closed by future research studies. The study has limitations which may affect the generalisability of the results since they can only be applied testing the validity and reliability of the developed conceptual model. The study adds to theoretical literature development by extending knowledge on the Reverse Logistics Model theoretical modelling framework since there is paucity of research that have directly applied the same model in agricultural inputs entrepreneurial marketing firms’ operational efficiency and sustainable competitive advantage. Practically, the study enhances the need for adoption of contemporary technologies to solve the current challenges facing agricultural inputs entrepreneurial marketing firms’ sustainable operational efficiency and competitive advantage in the marginalised areas, not only in developing and emerging economies, but also dotted around the world. The study contributes to the conceptual development, theoretical and practical policy directions applicable to any agricultural inputs entrepreneurial marketing firms. A model can be tested to prove its validity and reliability in future similar studies, using alternative methodologies.